2004
DOI: 10.1002/jmv.20094
|View full text |Cite
|
Sign up to set email alerts
|

SARS coronavirus induces apoptosis in Vero E6 Cells

Abstract: Severe acute respiratory syndrome (SARS) is an emerging infectious disease. Its etiological agent has been convincingly identified as a new member of family Coronaviridae (SARS-CoV). It causes serious damage to the respiratory system yet the mechanism is not clear. Infection-induced apoptosis or necrosis is suspected but no direct evidence for this yet exists. To date, Vero E6 cells are the only cell line that could be used to replicate the virus with obvious CPE (cytopathic effect) in vitro. It is known for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 50 publications
(92 reference statements)
3
98
0
Order By: Relevance
“…Apoptosis can also assist in the dissemination of viral particles and is the cause of tissue damage observed following many viral infections (Lyles, 2000). In SARS patients, apoptosis of cells of the lung epithelium has been observed, suggesting SARS-CoV-induced apoptosis to have a deleterious pathogenic role, leading to severe tissue damage (Yan et al, 2004). There are indications that apoptosis and the antiviral immune response may both contribute to the pathology in SARS patients (Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis can also assist in the dissemination of viral particles and is the cause of tissue damage observed following many viral infections (Lyles, 2000). In SARS patients, apoptosis of cells of the lung epithelium has been observed, suggesting SARS-CoV-induced apoptosis to have a deleterious pathogenic role, leading to severe tissue damage (Yan et al, 2004). There are indications that apoptosis and the antiviral immune response may both contribute to the pathology in SARS patients (Yang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This is usually a ciliated respiratory tract epithelial cell in the nasopharynx [12,67]. Thereafter, the mechanisms by which SARS-CoV causes disease can be separated into [68,69], apoptosis [68,70] or cell fusion to form syncytia [71]. Studies in mice have shown that there is a potent CD8 T-cell response with acute MHV infection [72], and that fulminant hepatitis can result from induced transcription of a novel fgl2 prothrombinase gene by the MHV nucleocapsid protein [73].…”
Section: Pathogenesismentioning
confidence: 98%
“…Besides lymphopenia, which is caused by the depletion of T lymphocytes by apoptosis, one study also reported apoptosis in the hepatocytes of three SARS patients who had liver impairment (6). Apoptosis was also observed in Vero E6 cells infected by SARS-CoV (31). Overall, these findings indicate that apoptosis plays an important role during SARS-CoV infection.…”
mentioning
confidence: 88%